Kritik Epistemologis Ignaz Goldziher Dan Joseph Schacht Terhadap Kitab Al-Muwattha’ Imam Malik - Mutaqin, Rizal Samsul; Muazar, Dandy Syauqy (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2022)
AbstractThis paper will try to see how the contribution of Imam Malik with his book al-Muwattha' to the development of hadith, and how the orientalist criticism of the book. In other words, how do orientalists criticize al-Muwattha' as the first generation of books in the writing of hadith. The research conducted in this study is a literature study using the book of al-Muwattha' Imam Malik as the primary source. The result of this research is Goldziher said that al-Muwattha' is more appropriately called a law book than a hadith book. Schact said: there is not a single authentic hadith contained in the book al-Muwattha', so that criticism has implications for doubting the authentic hadith as the word of the Prophet, and the Prophet there is not a single authentic hadith from the Prophet. AbstrakTulisan ini akan mencoba melihat bagaimana kontribusi Imam Malik dengan kitabnya al-Muwattha’ terhadap perkembangan hadis, dan bagaimana kritik orientalis terhadap kitab itu. Dengan kata lain, bagaimana orientalis mengkritik al-Muwattha’ sebagai kitab generasi pertama dalam penulisan hadis. Penelitian yang dilakukan dalam studi ini adalah studi literatur dengan menggunakan kitab al-Muwattha’ Imam Malik sebagai sumber primer. Hasil dari penelitian ini ialah Goldziher mengatakan bahwa al-Muwattha’ lebih tepat disebut kitab hukum daripada disebut kitab hadis. Schact mengatakan: tidak ada satupun hadis yang shahih yang terdapat dalam kitab al-Muwattha’, sehingga dari kritik itu berimplikasi pada keraguan terhadap hadis yang otentik sebagai sabda Nabi, dan Nabi tidak ada satu pun hadis yang otentik dari Nabi. Kata Kunci: Critics; Hadith Literature; Orientalists; Kitab al-Muwattha’.